PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA PADA MATERI STATISTIKA TERINTEGRASI NILAI-NILAI KEISLAMAN - Tia Ekawati; Bambang Sri Anggoro; Komarudin Komarudin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
This study aims to study the feasibility and convenience as well as the use of mathematical modules in statistical material integrated with developed Islamic values. The research and development procedures used were the development models of Borg and Gall. Expert validation is carried out by: (i) material experts; (ii) media experts; and (iii) religious experts. Small group trials were conducted on 6th grade students of MTs Al Huda Bandung Baru as many as 6 students and a field trial of 30 students. The results of this study consisted of a mathematics learning module on integrated statistical material Islamic values which included semester VIII statistical material 2. The feasibility of a mathematics learning module that was integrated with Islamic values based on validators, prospective research, and module attractiveness. interesting module that calculates N-Gain calculations included in the high category.